(untitled) (Albayan Scientific Journal, 2023)
There are many policies and global variables that affect and reflect the results on various aspects of human life at the economic level, social, cultural or political, as well as at the level of civilization, and most of these variables widespread phenomenon called globalization, The importance of research is that it is exposed to the phenomenon that results in many results in various economic, social, cultural and political that result in the absence of sound and scientific preparation to address them may result in some negative effects The research aims to shed light on: the different concepts of the concept of globalization and the different concepts of the concept of human resources management and the importance, objectives and functions of human resources management in light of globalization and the impact of globalization on human resources management The most important results of the research was the need to pay attention to the rehabilitation of human resources commensurate with the revolution of knowledge so that most of the skills and knowledge possessed by human resources commensurate with the requirements of globalization, and research found that meeting the challenges of globalization in the field of human resources management requires the development of structural strategies based on reconsideration In organizational policies, empowering employees, and redesigning jobs.